Influence of SiC on phase and microstructure of ZrB2 powders synthesized via carbothermal reduction at different temperatures. Issue 8 (1st June 2018) - Xie, Bingying; Ma, Li; Gao, Dezhi; Lin, Xiao; Liu, Yu; Zhang, Yujun; Gong, Hongyu
Abstract: ZrB2 powders were successfully prepared via carbothermal reduction of ZrO2 with H3 BO3 and carbon black under flowing argon. By introducing SiC species into reaction mixtures, the effects of SiC addition on phase composition and morphology of ZrB2 powders thermally treated at different temperatures were investigated. The resultant samples were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), and energy dispersive spectrometer (EDS). The highly pure ZrB2 with the mean size of 5 µm could be obtained at 1600 °C for 90 min and the grains presented columnar shapes. After addition of SiC, ZrB2 revealed relatively better crystallinity and finer particle size. Regular columnar ZrB2 grains ranging from 1 to 2 µm were seen existing after reaction at 1500 °C for 90 min.